The association between plasma C-peptide concentration and the risk of prostate cancer: a nested case–control study within a Japanese population-based prospective study. Issue 5 (September 2018) - Kiyabu, Grace Y.; Sawada, Norie; Iwasaki, Motoki; Yamaji, Taiki; Shimazu, Taichi; Sasazuki, Shizuka; Inoue, Manami; Tsugane, Shoichiro
Abstract : The association between plasma C-peptide concentration and prostate cancer is unclear. Inconsistency of results from previous studies motivates this study. Using the Japan Public Health Center-based Prospective study, 201 prostate cancer cases and 402 controls were matched by age, public health center area, residence, date and time of blood collection, and fasting duration before blood collection. Odds ratios (OR) and 95% confidence intervals (CIs) were estimated by conditional logistic regression models. Out of 201 cases, 144 were localized and 48 were advanced. The overall association between median plasma C-peptide concentration and prostate cancer was not significant (OR for the highest tertile=0.81, 95% CI: 0.43–1.56, P -trend=0.54). Although stratification of prostate cancer by stage indicated different effects of plasma C-peptide on localized and advanced cases, there was no association between plasma C-peptide concentration and advanced prostate cancer (OR=2.82, 95% CI: 0.30–26.36 for the highest category, P -trend=0.37) and localized cases (OR=0.49, 95% CI: 0.23–1.04 for the highest category, P -trend=0.06) for patients fasting at the time of blood collection. The association between plasma C-peptide concentration and prostate cancer risk differed by cancer stage. Differentiation of localized and advanced prostate cancer cases is crucial when investigating the association between plasma C-peptide concentration and the risk of prostate cancer.